A Multi-Scalar Analysis of the Politics Of Obsidian Consumption in the West Mediterranean (ca. 6th - 2nd millennia B.C.) - Freund, Kyle (My University, 2014)
This dissertation details and contextualizes the changing nature of obsidian circulation and use in the West Mediterranean from the sixth to second millennia B.C., with a particular focus on the reflexive relationship between obsidian consumption and long-term socio-economic processes. Central themes in this work include, a) the significance of exchange and long-distance relations in the creation and maintenance of social distinction, b) the specific role of obsidian circulation and consumption in these processes, and c) a longue durée investigation of the history of obsidian use and maritime activity in the West Mediterranean from the Neolithic through Bronze Age. Methodologically this is achieved through, a) the compilation and interrogation of a database of regional obsidian studies over the past 50 years, and b) the generation of new primary data via the typological analysis of 6,895 obsidian artifacts from 46 archeological sites in Sicily and Sardinia, 2,103 of which were also elementally characterized using X-ray fluorescence (XRF) spectrometry to determine their geological source. Central to this work is the idea that obsidian ‘characterization’ studies represent a powerful means of engaging with major social science questions, where a particular regional dataset can be used to contribute to debates of global significance. Thus, while the focus of this work is on obsidian consumption in the West Mediterranean, its implications are far-reaching.
Keywords: Archaeology; West Mediterranean Prehistory